Tuning the ground-state and excited-state interchromophore interactions in porphyrin-fullerene π-stacks - Chukharev, Vladimir; Tkachenko, Nikolai; Efimov, Alexander; Guldi, Dirk Michael; Hirsch, Andreas; Scheloske, Michael; Lemmetyinen, Helge (Journal of Physical Chemistry B, 2004)
Recently synthesized porphyrin-fullerene dyads with two separate linkers form a nearly symmetric complex with π-stack sandwich-like structure. The interchromophore interactions of such complexes can be fine-tuned by varying the linker lengths, which opens an opportunity to control physical and chemical properties of the dyads. Absorption spectroscopy emerged as a convenient means to register the interchromophore interactions: the spectra of the chromophores ground-state absorptions show appreciable perturbations and, more importantly, an additional absorption feature is discernible in the near-infrared region. Similarly, the emission spectra have a character typical for intramolecular exciplex. These new spectral features (i.e., absorption and emission) were attributed to a new electronic state, namely, an intramolecular preformed exciplex, featuring a common molecular orbital with a partial charge transfer (CT) character. From the mechanistic point of view, it is important that the preformed exciplex preceded the actual nonemitting charge separated (CS) state. The quantitative analysis of the CT absorption and the exciplex emission bands within the framework of the Marcus electron transfer (ET) theory allowed us to estimate the energy of the exciplex, ΔG°, the solvent or outer-sphere reorganization energy, λ the internal reorganization energy, λ , the energy of the vibrational mode, E , and the electronic coupling matrix element, V. Variation in the linker lengths shows that mainly the electronic coupling is affected by this structural modification, leaving the other parameters essentially unchanged. The strongest coupling, V = 450 cm (0.056 eV), was observed for the dioxyethyl type of linkers, whereas in the shorter, oxymethyl type, and longer, dioxypropyl type, dyads the couplings were much weaker (190 and 270 cm , respectively). Photodynamics of the dyads was studied in the femto-and picosecond time domains, using the emission up-conversion and absorption pump-probe techniques.